Preparation of Aryl(dicyclohexyl)phosphines by C–P Bond-Forming Cross-Coupling in Water Catalyzed by an Amphiphilic-Resin-Supported Palladium Complex - Hirai, Yoshinori; Uozumi, Yasuhiro (Synlett, 2017)
Aryl(dicyclohexyl)phosphines were prepared by a catalytic C–P bond-forming cross-coupling reaction of haloarenes with dicyclohexylphosphine under heterogeneous conditions in water containing an immobilized palladium complex coordinated to an amphiphilic polystyrene–poly(ethylene glycol) resin supported di(tert-butyl)phosphine ligand.
Keywords: phosphines; haloarenes; C–P bond; cross-coupling; aqueous media; polymer support; palladium